2006
DOI: 10.1111/j.1467-985x.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Model Choice in Time Series Studies of Air Pollution and Mortality

Abstract: Summary.Multicity time series studies of particulate matter and mortality and morbidity have provided evidence that daily variation in air pollution levels is associated with daily variation in mortality counts. These findings served as key epidemiological evidence for the recent review of the US national ambient air quality standards for particulate matter. As a result, methodological issues concerning time series analysis of the relationship between air pollution and health have attracted the attention of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
352
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 479 publications
(370 citation statements)
references
References 59 publications
(59 reference statements)
7
352
0
11
Order By: Relevance
“…The median value of temperature was defined as the baseline temperature (centering value) for calculating the relative risks. Akaike information criterion for quasi-Poisson (AIC-Q) models was used to choose the df (knots) for temperature and lag (Peng et al 2006;Gasparrini et al 2010). It was found that using 5 df for temperature and 4 df for lag produced the best model fit in the present study.…”
Section: Resultsmentioning
confidence: 80%
“…The median value of temperature was defined as the baseline temperature (centering value) for calculating the relative risks. Akaike information criterion for quasi-Poisson (AIC-Q) models was used to choose the df (knots) for temperature and lag (Peng et al 2006;Gasparrini et al 2010). It was found that using 5 df for temperature and 4 df for lag produced the best model fit in the present study.…”
Section: Resultsmentioning
confidence: 80%
“…In many community time series studies on the effect of PM on mortality, an additive Poisson log-linear model is fit to the time series of observed mortality (Kelsall et al, 1997;Daniels et al, 2000;Kim et al, 2003;Peng et al, 2004a). Under this model, the daily mortality counts are modeled as independent Poisson random variables with a time varying mean m t on day t given by…”
Section: Methodsmentioning
confidence: 99%
“…Population sensitivity to PM, age distribution, and especially different particle components may strongly affect the exposure-response relationships. In addition, inconsistent with several time series studies [17][18][19], we used the non-parameter Spearman correlation analysis (in SPSS software) for our data analysis. Most prior air pollution time-series studies have been based on the GAM model in S-PLUS.…”
Section: Discussionmentioning
confidence: 99%